High performing chemochromic hydrogen gas sensing using PVP encapsulated Pd: WO3 nanocomposites - Yeasmin, Rubaya; Duy, Le Thai; Han, Seungik; Park, Chiwan; Seo, Hyungtak (Sensors and Actuators B: Chemical, 2023)
This paper reports on a high performing hydrogen (H2) sensing technique that has a great importance in safe operation of H2 including production and storage. The developed H2 sensing nanocomposite is made of polyvinylpyrrolidone (PVP) encapsulated Pd:WO3. The optimized amount of palladium (Pd) nanoparticles expedites achieving eye-readable chemochromic responses in presence of H2 gas, whereas the quasi-reversible property is obtained by the air passivation of PVP. The developed nanocomposite exhibits a high sensitivity and excellent selectivity toward H2 gas. As a result, it shows a rapid color change from brown to bluish-gray with a maximum ΔE value of 40.34 (at 100% H2) in 10 s. The changed color remains visible even after removal of H2 and keeping the samples in air for more than 24 h. More importantly, this quasi-reversible performance with rapid response (10 s) and elongated recovery (> 24 h) is repeatable for multiple cycles, which is achieved for the first time using Pd:WO3. The nanocomposite exhibits long-term stability over 30 days (at ambient condition), as well as performs efficiently at different temperature and humidity conditions. Moreover, the developed nanocomposite can be used as powders, inks, paints, or coatings on different substrates that highlights its efficacy for making multimodal H2 sensing platforms.
Keywords: Chemochromic; Eye-readable; Hydrogen gas sensing; Hydrogen sensor; Palladium nanoparticles; Palladium: WO3; Polyvinylpyrrolidones; Quasi-reversible; Safe operation; Sensing techniques; Chemochromic; Eye-readable; Hydrogen sensor; Pd: WO3; Quasi-reversible